Pengaruh Green Accounting, Kinerja Lingkungan dan Ukuran Perusahaan Terhadap Nilai Perusahaan Industrial Periode 2023-2024 - Mie Mie; Sulia Sulia; Iskandar Muda Situmorang (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2026)
The Tobin's Q formula is a measure of company value that is considered more rational because it considers the liability element in its calculation. This model combines all elements of the company's debt and equity, thus focusing not only on investors but also on creditors. Sustainability issues have become a global concern with increasing awareness of climate change, environmental degradation, and limited natural resources. Global organizations such as the United Nations, through the Sustainable Development Goals (SDGs), encourage all sectors, including the business sector, to integrate environmental and social aspects into their business strategies. The purpose of this study is to identify and analyze the influence of Green Accounting, Environmental Performance, and Company Size on Company Value (Tobin's Q Formula). The sampling method used was purposive sampling, and 56 companies were obtained that met the research criteria. The research data came from the annual financial reports of industrial companies published on the Indonesia Stock Exchange during the 2023-2024 period. The data testing method used the SPSS application. The research results show that Green Accounting and Environmental Performance have no effect on company value. Company size has a significant effect on company value.